Fighting the bushfire in HCC trials - Schirmacher, Peter; Bedossa, Pierre; Roskams, Tania; Tiniakos, Dina G.; Brunt, Elizabeth M.; Zucman-Rossi, Jessica; Manns, Michael P.; Galle, Peter R. (Journal of hepatology, 2011)
One of the key strategies to improve the prognosis of HCC, beside prevention, is to diagnose the tumor in early stages, when the patient is asymptomatic and the liver function is preserved, because in this clinical situation effective therapies with survival benefit can be applied. Imaging techniques are a key tool in the surveillance and diagnosis of HCC. Screening should be based in US every 6 months and non-invasive diagnostic criteria of HCC based on imaging findings on dynamic-MR and/or dynamic-CT have been validated and thus, accepted in clinical guidelines. The typical vascular pattern depicted by HCC on CT and or MRI consists on arterial enhancement, stronger than the surrounding liver (wash-in), and hypodensity or hyposignal intensity compared to the surrounding liver (wash-out) in the venous phase. This has a sensitivity of around 60% with a 96-100% specificity. Major improvements on liver imaging have been introduced in the latest years, adding functional information that can be quantified: the use of hepatobiliary contrast media for liver MRI, the inclusion of diffusion-weighted sequences in the standard protocols for liver MRI studies and new radiotracers for positron-emission tomography (PET). However, all them are still a matter of research prior to be incorporated in evidence based clinical decision making. This review summarizes the current knowledge about imaging techniques for the early diagnosis and staging of HCC, and it discusses the most relevant open questions. - Hepatocellular carcinoma (HCC) represents approximately 85 to 90% of all primary liver cancers (PLC) and every year, more than 560,000 people are diagnosed as affected by this cancer. - The identification of risk factors for HCC prompted the creation of screening and surveillance programs in patients affected by chronic liver diseases with the aim of detecting HCC nodules as soon as possible and provide effective and hopefully curative therapy - A correct diagnosis is of paramount importance for the surveillance program as well as for the choice of the appropriate therapy. Both in the diagnosis of small HCC and in the choice of the therapy for locally advanced HCC the diagnosis must be certain. - Improvements of the radiological imagine techniques have surely enhanced both early diagnosis and tumor staging, allowing a reasonably accurate diagnosis, but cannot provide the certainty that in clinical practice is essential for an adequate workout. - Therefore, the histopatological definition of the tumor is imperative both for an appropriate therapy and for an accurate prognostic evaluation. - Modern multiphase diagnostic imaging allows diagnosis of hepatocellular carcinoma with high specificity in a large proportion of cases. Additional aspects of tumor biology also can be evaluated noninvasively through observation of tumor behavior (growth rate, satellites, vascular invasion) and other indicators of tumor biology (avid uptake of fluorodeoxyglucose, high circulating levels of tumor markers such as alphafetoprotein). Routinely requiring biopsy confirmation for diagnosis of HCC exposes many patients to unnecessary risk, may delay diagnosis, and in some cases leads to withholding of potentially beneficial treatment. Biopsy for assessment of tumor molecular markers is promising but remains investigational. When diagnosis of HCC is clinically evident by imaging criteria, tumor biopsy should not be required prior to initiating treatment.